Interaction of Diversity: An Analysis of the Understanding, Needs, and Challenges of Religious Values in a Multicultural Society - Hyangsewu, Pandu; Abdillah, Hilman Taufik; Rahmania, Puput; Hayatunnisa, Hayatunnisa; Sudaryat, Muhamad Ridwan (Mafapress - Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) IPMAFA Pati, 2025)
The motto